Japanese Monsters and Yōkai in Videogames - Rachael Hutchinson (Education About Asia, 2026)
Japanese videogames frequently feature monsters and yōkai—supernatural beings drawn from folklore, mythology, and religious belief—yet their cultural significance is often overlooked in discussions of global game culture. This article provides an accessible overview of Japanese monsters and yōkai in videogames, situating them within broader historical, social, and aesthetic contexts. Through case studies of three globally popular titles—Pokémon Scarlet and Violet, Ōkami, and The Legend of Zelda: Breath of the Wild—the article examines how yōkai-inspired creatures function within gameplay mechanics, narrative worlds, and visual design. It explores how players encounter monsters as both adversaries and allies, and how mechanics such as collection, combat, befriending, and elemental systems encourage engagement with culturally specific knowledge. Drawing on folklore studies, game studies, and media scholarship, the article highlights the ways in which videogames act as conduits for Japanese culture, while also addressing issues of cultural packaging for export and the appropriation of Indigenous beliefs for entertainment. The article includes pedagogical resources and suggested classroom activities, demonstrating how videogames can be used effectively to teach about Japanese culture, mythology, and media in interdisciplinary educational settings.
Keywords: Japan; videogames; folklore; mythology; Pokémon; Ōkami; Zelda